A Family of Externally-Functionalised Coordination Cages - Garrett D. Jackson; Max B. Tipping; Christopher G. P. Taylor; Jerico R. Piper; Callum Pritchard; Cristina Mozaceanu; Michael D. Ward (Chemistry, 2021)
New synthetic routes are presented to derivatives of a (known) M8L12 cubic coordination cage in which a range of different substituents are attached at the C4 position of the pyridyl rings at either end of the bis(pyrazolyl-pyridine) bridging ligands. The substituents are (i) –CN groups (new ligand LCN), (ii) –CH2OCH2–CCH (containing a terminal alkyne) groups (new ligand LCC); and (iii) –(CH2OCH2)3CH2OMe (tri-ethyleneglycol monomethyl ether) groups (new ligand LPEG). The resulting functionalised ligands combine with M2+ ions (particularly Co2+, Ni2+, Cd2+) to give isostructural [M8L12]16+ cage cores bearing 24 external functional groups; the cages based on LCN (with M2+ = Cd2+) and LCC (with M2+ = Ni2+) have been crystallographically characterised. The value of these is twofold: (i) exterior nitrile or alkene substituents can provide a basis for further synthetic opportunities via ‘Click’ reactions allowing in principle a diverse range of functionalisation of the cage exterior surface; (ii) the exterior –(CH2OCH2)3CH2OMe groups substantially increase cage solubility in both water and in organic solvents, allowing binding constants of cavity-binding guests to be measured under an increased range of conditions.